"This Day We Marched Again" : A Union Soldier's Account of War in Arkansas and the Trans-Mississippi - Haas, Jacob, 1840-1906 (Book collections on Project MUSE., 2014)
Mark K. Christ is outreach director for the Arkansas Historic Preservation Program at the Department of Arkansas Heritage and has led the agency's battlefield preservation efforts since 1992. Christ is the author or editor of numerous books on Arkansas Civil War history, including The Die Is Cast: Arkansas Goes to War, 1861; Rugged and Sublime: The Civil War in Arkansas; and "All Cut to Pieces and Gone to Hell": The Civil War, Race Relations, and the Battle of Poison Spring. A graduate of the University of Arkansas at Little Rock with a master's degree from the University of Oklahoma, Christ l.